2022
DOI: 10.1101/2022.05.11.491515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated Single-Cell Genotyping and Chromatin Accessibility ChartsJAK2V617FHuman Hematopoietic Differentiation

Abstract: In normal somatic tissue differentiation, changes in chromatin accessibility govern priming and commitment of precursors towards cellular fates. In turn, somatic mutations can disrupt differentiation topologies leading to abnormal clonal outgrowth. However, defining the impact of somatic mutations on the epigenome in human samples is challenging due to admixed mutated and wildtype cells. To chart how somatic mutations disrupt epigenetic landscapes in human clonal outgrowths, we developed Genotyping of Targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 182 publications
0
15
0
Order By: Relevance
“…Cell-intrinsic consequences may arise directly from the somatic mutation while extrinsic, indirect consequences may arise from altered cell-cell interactions or secreted immune effectors. Several technologies have sought to close this gap by selectively amplifying the mRNA transcriptome and using this to genotype cells [11][12][13][14] . This approach is effective in HSPCs that express DNMT3A and TET2, with a genotyping efficiency rate of ~1-9%; however, genotyping is less efficient in cells that do not express these genes, such as fully differentiated cells in the peripheral blood 12,13,15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-intrinsic consequences may arise directly from the somatic mutation while extrinsic, indirect consequences may arise from altered cell-cell interactions or secreted immune effectors. Several technologies have sought to close this gap by selectively amplifying the mRNA transcriptome and using this to genotype cells [11][12][13][14] . This approach is effective in HSPCs that express DNMT3A and TET2, with a genotyping efficiency rate of ~1-9%; however, genotyping is less efficient in cells that do not express these genes, such as fully differentiated cells in the peripheral blood 12,13,15 .…”
mentioning
confidence: 99%
“…Several technologies have sought to close this gap by selectively amplifying the mRNA transcriptome and using this to genotype cells [11][12][13][14] . This approach is effective in HSPCs that express DNMT3A and TET2, with a genotyping efficiency rate of ~1-9%; however, genotyping is less efficient in cells that do not express these genes, such as fully differentiated cells in the peripheral blood 12,13,15 . Another method, TARGET-seq, has sought to amplify specific, previously identified variants in mutated cells with high-efficiency genotyping along with gene expression, albeit lower throughput 16,17 .…”
mentioning
confidence: 99%
“…More recent studies combining at the single cell level the genotyping of specific genes with the analysis of chromatin accessibility showed that JAK2 V617F mutated HSPCs exhibited specific proinflammatory signatures with accessibility to DNA motifs binding NF-kB or JUN/FOS factors. This technique also allowed to highlight epigenetic modifications specific to mutated erythroid or megakaryocytic progenitors, demonstrating that the consequences of the mutations are different according to the differentiation state and cellular context [55]. A similar approach showed that DNMT3A mutations resulted in myeloid over lymphoid bias and in expansion of immature myeloid progenitors primed toward megakaryocytic-erythroid fate, and also demonstrated the dysregulated expression of lineage and leukemia stem cell markers with the preferential hypomethylation of polycomb repressive complex 2 targets [56].…”
Section: Reconstruction Of Mpns Clonal Architecture At the Transcript...mentioning
confidence: 99%
“…An alternative approach uses a combination of genotyping of targeted loci with single-cell ChA (GoT-ChA) and was able to show both cell-intrinsic and cell state-specific shifts within mutant human hematopoietic HSPCs in the context of JAK2V617F-mutated MPN. 113 Contributing further to MPN biology by using scRNA-Seq and genotyping of JAK2V617F mutation status showed increases in the expression of interferon-response genes. 99,114 In human cells, genotyping of the mitochondrial genome at the single-cell level has been recently combined with scATAC-Seq to study cell population dynamics and clonal properties in cancer of the hematopoietic system, showing that it is possible to infer subclonal population structures using natural genetic mitochondrial DNA barcodes.…”
Section: Multiomicsmentioning
confidence: 99%
“…An alternative approach uses a combination of genotyping of targeted loci with single-cell ChA (GoT-ChA) and was able to show both cell-intrinsic and cell state-specific shifts within mutant human hematopoietic HSPCs in the context of JAK2V617F -mutated MPN. 113 Contributing further to MPN biology by using scRNA-Seq and genotyping of JAK2V617F mutation status showed increases in the expression of interferon-response genes. 99,114…”
Section: Single-cell Omic Approaches To Elucidate the Heterogeneity O...mentioning
confidence: 99%